2016
DOI: 10.18860/ling.v10i2.3132
|View full text |Cite
|
Sign up to set email alerts
|

The Transformation of English as a Global Language in the Future

Abstract: Abstract:It is argued that English as a global language has some advantages to people around the world. One of the advantages is that English language is used as a tool of communication, empowerment and unification of people in the global community. In other words, English plays a very important role to unite all the people around the globe regardless their nationalities, cultural backgrounds, or races. However, for some scholars, English is seen as a potential threat to linguistic diversity in the world (Flor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…The English language is considered a lingua franca due to its dominance in many social, economic, scientific and political activities (Crystal, 2004;Nishanti, 2018;Pandarangga, 2015;Pennycook, 2014;Reddy, 2016). Reports have shown that about 750 million people use English as a second language (ESL), and it is prioritised in around 70 countries in the world (Reddy, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The English language is considered a lingua franca due to its dominance in many social, economic, scientific and political activities (Crystal, 2004;Nishanti, 2018;Pandarangga, 2015;Pennycook, 2014;Reddy, 2016). Reports have shown that about 750 million people use English as a second language (ESL), and it is prioritised in around 70 countries in the world (Reddy, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, English language learners have reached 1 billion, while roughly 2 billion people have mastered the language, with an estimation that half of the world population might be English proficient in the next few decades (English Cultural Council as in Xue & Zuo, 2013). The English language has also become the medium of instruction in many higher education institutions, and it has also been used as a criterion with which students secure admissions into tertiary education programs (Pandarangga, 2015). As such, English communication competency is considered among the highly significant requirements of university graduates' quality in Asia (UNESCO, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…English language is a global language used in communications, interactions, and information transfer (Pandarangga, S. 2016). In order to be proficient in English language one has to be capable of listening, speaking, reading, and writing in English language.…”
Section: Introductionmentioning
confidence: 99%
“…Using English to communicate may also help people to know, understand and respect each other particularly those who have different backgrounds such as languages, cultures and ethnics (Mukminin, Ali, & Ashari, 2015). Besides, it is as a bridge to solve differences such as conflicts across the country globally, these conflicts are mostly avoidable with mediation and negotiation through English as a medium of communication (Pandarangga, 2015). English as a global language has united and connected all the people worldwide in terms of communication and it solve differences (Habibi, Mukminin, Najwan, Sofwan, Haswindy, Marzulina, Sirozi, & Harto, 2018;Makmur, Mukminin, Ismiyati, & Verawati 2016).…”
Section: Introductionmentioning
confidence: 99%